(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2024)
The study is based on the study of IFRS 16 and the extent to which it is compatible with the Income Tax Law No. (113) for the year 1982 As a first step to adopt the General Authority for Taxation (IFRS) , Therefore , the research aims to identify the areas of difference and harmony between the tax system in Iraq with the requirements of IFRS, and propose a framework for achieving harmony between them. By theoretical and practical study, a number of conclusions were reached regarding the subject and the selected sample. The most important of which is the inconsistency of the Iraqi income tax law with IFRS requirements, since it began in the 1980s when the country’s economic direction was socialist on the one hand, and (1), (2), (3) and (4) Rent. The two researchers were able to provide a set of recommendations based on the conclusions contained therein. The most important of which is to speed up the process of amending the tax system in Iraq to achieve international accounting compatibility in terms of preparation and implementation and humiliation of all obstacles facing reform As did the Egyptian and Jordanian legislators.